Memandang Kebiasaan Membuang Sampah dan Peran Dinas Kebersihan dengan Perspektif Struktural Fungsional di Kecamatan Medan Marelan, Kota Medan - Rakha Dimas Praditya; Rahma Hayati Harahap (Jurnal Intervensi Sosial, 2023)
This research aims to determine the correlation between functional structural theory and people's habits in throwing away any rubbish resulting from the habit of throwing rubbish carelessly on the social environment in Medan Marelan District, Medan City. The research method used is the field observation method. Where research results are obtained through direct observation using observation guidelines, namely directly observing the object being studied. The results of the research show that the influence of waste on the social environment is: in terms of health, the presence of various diseases that attack from accumulated waste, the city government manages waste so that it is easy to sort it by providing facilities and advice on waste disposal and workers transporting waste. In the social aspect of society, the influence of society on communication has increased, in contrast to before the improvements. In terms of accessibility, the impact has been felt by the community, especially the surrounding community. The community is certainly greatly helped by the role of the cleaning service. For example, it won't take long for them to throw away their rubbish to get to the landfill because there are already rubbish workers from the Medan city sanitation service close to where they live. Finally, in terms of the environment, the impact of littering has shown a significant influence because after this habit, rivers, roads and drainage have accumulated rubbish.